Prophylactic Dermatologic Treatment of Afatinib-Induced Skin Toxicities in Patients with Metastatic Lung Cancer: A Pilot Study - Maria Pia Fuggetta; Maria Rita Migliorino; Serena Ricciardi; Giorgia Osman; Daniela Iacono; Alvaro Leone; Alessandra Lombardi; Giampietro Ravagnan; Stefania Greco; Daniele Remotti; Maria Concetta Pucci Romano (Scientifica)
Background. Severe skin rash is listed among important side effects of EGFR tyrosine kinase inhibitors. Polydatin (PD), a glycosylated polyphenol, is endowed with anti-inflammatory activity in human epidermal keratinocytes. Objective. This study evaluated the effect of topical application of a moisturizer containing PD to prevent skin rash in patients with mutated non-small cell lung cancer (NSCLC) treated with afatinib. Materials and Methods. Eligible NSCLC patients with metastatic disease were treated with first-line afatinib 40 mg/die. One day before starting systemic therapy, all patients received topical administration of a 1.5% PD-based cream b.i.d. every day until the end of afatinib treatment. Results. Out of 34 treated patients, the incidence of skin rash (all grades) was 41.2% and grade 2 rash was 20.6%, and grade 3 rash was not observed in any of the patients. None of the patients discontinued therapy for toxicity. The mean duration of treatment was 6.4 months, calculated from the time treatment was started to the date treatment was stopped. Conclusion. The results showed that a PD-based cream can reduce the incidence of grade ≥2 skin toxicities in patients treated with afatinib. Clinical study registration number: Prot. No. 130/CE Lazio 1 Italy.